The Chinese foreign policy towards the Arab region (2012 – 2017) (قضايا سياسية, 2023)
China has paid great attention to the Arab region, especially in the economic sphere. China’s interests have increased at the political, geographical, energy and security levels, in order to achieve the goals of Chinese foreign policy that are characterized by peacefulness, independence, mutual benefit and common prosperity. China needs its relationship with Arab countries in order to achieve its international ambition and to practice its role as a major global power.